Content to share with expectant fathers: Views of professionals focused on father involvement. (March 2019) - Aqil, Anushka; Allport, Brandon S.; Johnson, Sara B.; Nelson, Timothy; Labrique, Alain B.; Marcell, Arik V.
Highlights: Key content was identified to share with expectant fathers during maternity care. Key content relates to infant and partner support. Additional content relates to planning/participating in birth and father support. This shared content can benefit all members of the family triad. Abstract: Objective: To examine whether there is a consensus on what guidance to share with expectant fathers from the prenatal through early infancy period among a multidisciplinary group of professionals with expertise on father involvement. Design: Consensus-building approach using mixed methods involving two rounds of data collection. In Round 1, participants were requested to individually generate content as text messages to share with expectant fathers that a father should know or do for his infant, his partner, and himself starting prenatally and through early infancy. A content analysis of Round 1 data was conducted to identify domain content to share with fathers. During Round 2, experts were asked to rate their perceived level of importance of the content generated in Round 1. Descriptive statistics, including frequencies, means, and standard deviations were calculated for Round 2. Setting: Electronic survey. Participants: Nine multidisciplinary professionals with expertise on father involvement, representing psychology, pediatrics, nursing/midwifery, and sociology. Measurements and findings: During Round 1, participants individually generated 302 message content items across domains in the following contexts: plan for/participate in birth ( n = 71); his infant ( n = 95); his partner ( n = 107); and himself ( n = 38). During Round 2, participants achieved greatest consensus in more content items in two contexts: infant support and partner support. For infant support, content domains that participants perceived it important to share with for fathers included: knowledge about signs of infant illness, feeding, sleep patterns, and impact of second hand smoke/drug use; training on providing newborn care; and taking action including participating in infant care, providing verbal stimulation, engaging in age-appropriate play and physical contact, supporting safe sleep, and making/attending doctor appointments. For partner support, content domains that participants perceived it important to share with fathers included: communicating with partners with regular check-ins, and about parenting styles and shared responsibilities, signs/symptoms of maternal depression, and hopes/dreams for infant; and taking actions to support partner's physical and emotional health and breastfeeding. Although less content was generated in the other two contexts - plan for/participate in birth and father support - participants achieved consensus on some content in these domains as being important to share with fathers. Key conclusions: Despite lack of professional guidelines for expectant fathers, experts generally agreed on the content that should be shared with expectant fathers from pregnancy through early infancy, especially in the domains of infant support and partner support. Implications for practice: This study can assist clinicians and practitioners on guidance to share with expectant fathers during their partner's pregnancy and the early postnatal period. Dissemination of such guidance to fathers can assist in benefiting all members of the family.